2022
DOI: 10.1111/jasp.12923
|View full text |Cite
|
Sign up to set email alerts
|

How exposure to real conspiracy theories motivates collective action and political engagement? Τhe moderating role of primed victimhood and underlying emotional mechanisms in the case of 2018 bushfire in Attica

Abstract: Conspiracy theories concern milestone events, mobilizing various explanations. However, there is still emerging research on how conspiracy beliefs mobilize normative and nonnormative collective action, as well as political engagement and what the emotional underpinnings of such effects are. We conducted two experimental studies (Study 1, N = 301 and Study 2, N = 328) on exploring the relationship between exposure to conspiracy theories and normative, nonnormative collective action and political engagement, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…In addition, we found that this conspiracy-driven support for change among the right (but not the left) was even reflected in normative collective action intentions. This finding adds to previous research that links belief in conspiracy theories to collective action intentions but yielded somewhat inconsistent findings with regard to normative versus nonnormative forms of collective action (Gkinopoulos & Mari, 2022;Imhoff & Bruder, 2014). In addition, it might be carefully interpreted as a sign that right wingers with a strong conspiracy mentality support population-based social change.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, we found that this conspiracy-driven support for change among the right (but not the left) was even reflected in normative collective action intentions. This finding adds to previous research that links belief in conspiracy theories to collective action intentions but yielded somewhat inconsistent findings with regard to normative versus nonnormative forms of collective action (Gkinopoulos & Mari, 2022;Imhoff & Bruder, 2014). In addition, it might be carefully interpreted as a sign that right wingers with a strong conspiracy mentality support population-based social change.…”
Section: Discussionmentioning
confidence: 48%